Short Sampling Periods: A New Setup to Evaluate the Change in the Chemical Composition of Fog at High Time Resolution - Bettina Breuer; Neng-Huei (George) Lin; Weiti Tseng; Yen-Jen Lai; Otto Klemm (Tellus: Series B, Chemical and Physical Meteorology, 2023)
This study used a water volume-based sampling method in combination with an active fog collector (modified Caltech design) to collect fog water samples during three intensive operation periods at two mountainous study sites in Taiwan. The new setup employed a sample-volume controlled system that dosed the fog water into 10 ml aliquots, which were then collected with a commercial laboratory auto-sampler. We collected fog water samples about 10 times more frequently (median sampling period 3 minutes and 45 seconds) than with traditional sampling schemes. Notably, up to over 200 samples were collected within a single fog event lasting 13 hours. The results showed that the intra-event variabilities of pH (up to over 2 units), conductivity (range almost 1000 μS cm–1), and ion concentrations were generally higher than the inter-event variability. The variabilities exhibited particularly fast changes during phases of fog onset and dissolution; in contrast, the centers of the passing clouds at our mountain research sites were rather homogeneous. Overall, our new method showed a marked improvement in sampling speed over traditional methods.